Respuesta :

Answer:

The answer is option a

Step-by-step explanation:

   Given,

    f(x) = [tex]\sqrt{x^{2}-4 }[/tex]

    g(x) =  3x - 2      

    By substituting g(x) in f(x) we get

    f(g(x)) = [tex]\sqrt{(3x-2)^{2} -4}[/tex]

    By differentiating with respect to we get

    [tex]\frac{\mathrm{d}\sqrt{(3x-2)^{2} -4}}{\mathrm{d} x}[/tex] =  [tex]1/2\sqrt{(3x-2)^{2}-4} [/tex]×2×(3x-2)×3

    By using chain rule we get this equation

    [tex]{\mathrm{d}f(g(x))}/{\mathrm{d} x}[/tex] = [tex]1/2\sqrt{(3x-2)^{2} -4} [/tex]×2×(3x-2)×3

    Substituting x = 3 we get

     [tex]{\mathrm{d}f(g(x))}/{\mathrm{d} x}[/tex] = 7/[tex]\sqrt{5}[/tex]

    Answer is option a

   

   

Answer:

OPTION A: [tex]$ \frac{7}{\sqrt{5}} $[/tex]

Step-by-step explanation:

Given: f(x) = [tex]$ \sqrt{x^2 - 4} $[/tex] and g(x) = 3x - 2

We are to find f(g(x)).

f(g(x)) = f(3x - 2)

Substituting 3x - 2 in place of x in f(x), we get

f(g(x)) = [tex]$ \sqrt{(3x - 2)^2 - 4}$[/tex]

[tex]$ \implies \sqrt{9x^ 2 - 12x + 4 - 4} = \sqrt{9x^2 -12x} $[/tex]

Differentiating this we get:

[tex]$ f(g(x))^' = \frac{1}{2} (9x^2 - 12x)^{\frac{-1}{2}}} \times (18x - 12) $[/tex]

At x = 3,

[tex]$ f(g(3))^' = \frac{1}{2}[9(3)^2 - 12(3)]^{\frac{-1}{2}}} \times [18(3) - 12] $[/tex]

[tex]$ = \frac{1}{2} [81 - 36]^{\frac{1}{2}}} \times 42 $[/tex]

[tex]$ = \frac{21}{\sqrt{45}} $[/tex]

[tex]$ \frac{21}{3\sqrt{5}} $[/tex]

[tex]$ \frac{7}{\sqrt{5}}} $[/tex]

Therefore, the answer is 7/√5.